Pengaruh Tingkat Hunian Hotel, Jumlah Wisatawan, dan Jumlah Objek Wisata terhadap Pendapatan Sektor Pariwisata di Kota Semarang Tahun 2000-2020 - Devina Amelia; Fitrie Arianti (Diponegoro Journal of Economics, 2023)
This study aims to determine the income of the tourism sector through the factors that can influence it, namely the hotel occupancy rate, the number of tourists, and the number of tourist objects as independent variables on the income of the tourism sector in Semarang City in 2000-2020. Sources of data used are secondary data obtained from documentation. The data analysis technique used multiple linear regression analysis. The results of the study obtained a coefficient of determination of 0.193, meaning that the hotel occupancy rate, the number of tourists, and the number of tourist objects can explain the variation in tourism sector income by 19.3 percent. The results of the hypothesis test obtained that hotel occupancy has a significant effect on tourism sector income, the number of tourists has no significant effect on tourism sector income, and the number of tourist objects has no significant effect on tourism sector income.